Determining the direct benefits and costs of prescribed burning : a case study of the Langeberg Mountain veld area, Western Cape, South Africa - Muyima, Gracia (Stellenbosch : Stellenbosch University, 2025)
Thesis (MScAgric)--Stellenbosch University, 2025.